Sistem Pendukung Keputusan Penentuan Beasiswa Pada SMP Al-Khairiyah Cilegon-Banten - Khasan Asrori; Darpi Darpi; Sawitri Nurhayati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The Decision Support System for determining scholarships at SMP Al-Khairiyah Cilegon Banten is an information technology that assists in making decisions regarding awarding scholarships to students. The problem with defining grants is that they often have the wrong purpose. In the process of selecting scholarships recipients from similar institutions that have been carried out so far, there are difficulties in selecting scholarship recipients because of the many criteria involved in awarding scholarships making it difficult to make decisions about awarding scholarships, and it also takes a long time.The purpose of this research is to create a decision support system to identify scholarship recipients. The research method used is Multi Criteria Decision Making (MCDM). Designed with design tools such as Data Flow Diagram (DFD), Entity Relationship Diagram (ERD),file specifications, HIPO, and user interface designs. As for the implementation using Visual Basic 2012 and the Microsoft Access 2019 database. From the results of this research a decision support system was created at SMP Al-Khairiyah, it is hoped that through this system the determination of scholarships can assist in making decisions to be faster, efficient, and directed. The system also uses available information to make more effective decisions. Keywords—Decision Support System, MCDM Method, Scholarship